Upaya Meningkatkan Kemampuan Membaca Permulaan melalui Media Flash Card pada Kelompok Belajar TK B Usia 5-6 Tahun - Ayunda Fauziah, Najma; Erhamwilda, Erhamwilda; Hakim, Arif (Bandung Conference Series: Early Childhood Teacher Education, 2025)
Abstract. This study aims to improve early reading skills among children aged 5–6 years in TK B learning groups through the use of flash card media. The research employed a quasi-experimental method with a pre-test and post-test design. The study subjects consisted of two groups: an experimental group that used flash cards and a control group that applied conventional teaching methods. The findings revealed a significant improvement in early reading skills among children in the experimental group following the implementation of flash cards. In contrast, the control group showed only minimal improvement in the post-test results. Based on data analysis, it can be concluded that the use of flash cards is significantly effective in enhancing early reading skills in young children. This study is expected to contribute to the development of reading instruction methods in early childhood education. Abstrak. Penelitian ini bertujuan untuk meningkatkan kemampuan membaca permulaan anak usia 5-6 tahun di kelompok belajar TK B melalui penggunaan media flash card. Metode yang digunakan dalam penelitian ini adalah quasi eksperimen dengan desain pre-test dan post-test. Subjek penelitian terdiri dari dua kelompok yaitu kelompok eksperimen yang menggunakan flash card dan kelompok control yang menggunakan metode pembelajaran konvensional Hasil penelitian menunjukkan bahwa terdapat peningkatan signifikan dalam kemampuan membaca permulaan anak setelah penggunaan media flash card. Sebaliknya, kelompok control post-test menunjukkan peningkatan yang minimal. Dari hasil analisis, dapat disimpulkan bahwa penggunaan media flash card secara signifikan efektif dalam meningkatkan kemampuan membaca permulaan anak usia dini. Penelitian ini diharapkan dapat memberikan kontribusi bagi pengembangan metode pembelajaran membaca pada pendidikan anak usia dini.